Thrombosis in systemic lupus erythematosus: a French collaborative study. Issue 6 (June 1991) - Montes de Oca, M A; Babron, M C; Blétry, O; Broyer, M; Courtecuisse, V; Fontaine, J L; Loirat, C; Méry, J P; Reinert, P; Wechsler, B
Abstract : A retrospective study was undertaken of 120 children with systemic lupus erythematosus (SLE) seen in Paris and its immediate suburbs who fulfilled at least four of the American College of Rheumatology diagnostic criteria for SLE, and in whom the disease was diagnosed before the age of 16 and between January 1975 and December 1987. Eleven of these children (eight girls and three boys) all more than 10 years of age (mean follow up 8.1 years; range 3-13) had thrombotic episodes (9%). Thrombosis was one of the presenting signs in seven patients; in five it was associated with typical symptoms of SLE, and in the other two the thrombotic episode was isolated and diagnosis of SLE was delayed one and three years. Of a total of 16 thrombotic episodes (six of which were recurrent), 14 involved the leg veins, and in four there was associated pulmonary embolism. There were two episodes that affected cerebral arteries. The American College of Rheumatology diagnostic criteria for SLE as well as the incidence of lupus anticoagulant, positive direct Coombs test, and vasculitis in this group of patients was compared with the incidence in patients with SLE but no thrombosis. Only lupus anticoagulant was significantly associated with thrombotic episodes: eight of 11 (73%) of patients with SLE and thrombotic (arterial or venous) episodes had lupus anticoagulant compared with only 10 of 74 patients (14%) with no history of thrombotic events in the same age group.